Persistent chest pain in young male patient: Jackhammer esophagus treated with peroral endoscopic myotomy. Issue 2 (12th March 2019) - Tabuchi, Maiko; Minami, Hitomi; Akazawa, Yuko; Ogihara, Kumi; Kitayama, Moto; Hashiguchi, Keiichi; Matsushima, Kayoko; Yamaguchi, Naoyuki; Ohnita, Ken; Takeshima, Fuminao; Inoue, Haruhiro; Nakao, Kazuhiko
Abstract : Initial esophagogastroduodenoscopy (EGD) shows segmental contractions right above the gastro‐esophageal junction, which may be related to the symptoms. A clip was applied during a previously performed manometry. There was no evidence of stricture. High‐resolution manometry before peroral endoscopic myotomy shows a hypercontractile esophagus expressed as distal contractile integral > 8000 mmHg cm s two times out of 10.